Analisando imagens: Um ensaio sobre a criação de fontes narrativas para compreender os Grupos Escolares - Garnica, Antonio Vicente Marafioti [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2010)
This paper is an essay on how photos can be analysed and used to create narratives which may serve as resources for historical studies about school practices. As an exercise, we deal with six old photographs taken in Grupos Escolares, a Brazilian educational institution founded in the last decade of the 19th Century and extinguished in the 1970's. According to some authors, these schools represented the beginning of the public educational system in Brazil.
Analysing photographs: An essay on the creation of narrative sources to understand school practices in Grupos Escolares
Keywords: Analysis; Brazilian ancient educational institutions (Grupos Escolares); Photography